Environmental awareness and attitudes among students: Survey evidence from Colombia and Nicaragua - Díaz, Manuel Francisco; Burkart, Stefan (2021)
During 2016 and 2017, we collected data from students of higher education in Colombia and Nicaragua with the objective of identifying social perceptions about global climate change (GCC). For this purpose, we used a survey composed of: Knowledge of climate change, personal efficacy, trust, environmental behavior and New Environmental Paradigm (NEP). The results show that the level of students’ understanding of the GCC phenomenon is mostly moderate and the social factors, environmental attitude, trust and personal efficacy have influence on these variables.